Antiretrovirals If Possible, But Not Necessarily (Hekima Review, 2006)
In February, AJAN welcomed Franciscans International, represented by Fr. Michael Perry, OFM, and Mr. Yao Agbetse, for a visit and good exchange about Church efforts to combat HIV and AIDS in Africa. Later, Fr. Perry wrote back: “Thank you for the opportunity to meet with you and to learn of your work and that of others who are engaged in the battle against HIV/AIDS. I found your comments about access to ARVs (antiretrovirals) ‘interesting’. You seem to place great emphasis on the caring/receiving/supporting community as the essential and principal ‘therapeutic’ strategy for those living with HIV or AIDS (PLWHA).